Evaluation of Husbandry Practices and Constraints for Cattle Fattening in Bench Maji Zone, South West Ethiopia - Assefa, Hailu (International Journal For Research In Agricultural And Food Science, 2020)
A study was conducted with the objective to evaluate cattle fattening husbandry practices and constraints in Bench Maji zone south western Ethiopia through 11 focus group discussions, field observation and interviewing 301 cattle fattener households which were selected purposively by pre-tested, semi structured questionnaire. Cut and carry (46.44%), tethering (24.0%) and free grazing fattening (29.56%) cattle fattening system were practiced. The major feed resources in the study area were Weeds from crop land and Thinning and leaf parts of maize(Zea Mays) (43.5%); Aftermath grazing and Leaf and stem parts of Este pathos (Draceana steudeneri) (24.4); Natural grass and stem and leaf parts of enset (Ensete ventricosum)23.26%); and Leaf and stem parts of Banana(Musa sapientum) and sugar cane(Sacharum Officinarum) (10.1%). From the total of household respondents the supplementary feed sources which was used for fattening purpose were Roasted/cooked maize(Zea Mays) grain, Cooked kocho(Ensete ventricosum) and Taro( Colocasia esculenta), and Table salt, 36.75%, 31.27% and 31.52% respectively. The duration of fattening, umber of fattening cycle per year and number of cattle per cycle was 3.4 month, 2.05 and 3.8 respectively. Selection indexes 0.57, 0.48, 0.33, 0.81 shows physical Appearance/shape, Body Size, sex and Age respectively were fattening cattle selection criteria in the study zone. The current result shows that 31.11% provide houses or some form of shelter to their fattening cattle. The performance of beef cattle is challenged by awareness (0.47), feed (0.184), lack of extension service (0.15%) and cattle disease (0.10%) in order of importance. Therefore the great intention is needed to improve cattle fattening system, through awareness creation/extension service, improved forage development and locally resourced feeds utilization and preservation intervention. Similarly experimental researches on chemical composition of used local feed resources and large scale research on beef marketing and their contribution to food security in the area is needed.